Mental health among people in prison at the time of COVID-19: all bad news?. (20th October 2021) - Plugge, E
Abstract: Introduction: Institutional changes in prisons in response to the COVID-19 pandemic have affected the mental health of those who live and work in prisons. Infection prevention and control (IPC) measures have been implemented in prisons throughout the world to protect imprisoned people from COVID-19 and minimise harm to them and the communities in which they are situated. These efforts have been focused on minimising the risk of infection with an emphasis on individual's physical health. The current international evidence on the broader aspects of imprisoned people's wellbeing during the pandemic mostly comprises opinion pieces. These emphasise the likely negative effects of isolating imprisoned people; the picture however is likely to be more nuanced. Methods: One national study across England used quantitative and qualitative methods to examine rates of self-harm in prisons and understand some of the underlying reasons. Another national study measured mental wellbeing, using the Warwick Edinburgh Mental Wellbeing Scale (WEMWBS), in staff and imprisoned people during the pandemic. Results and discussion: Self-harm rates have varied across the prison estate with the most notable differences seen between men and women's prisons and this is explained by several factors, including perceived safety and support networks. There are notable differences between the mental wellbeing of prison residents and staff. Conclusions: The implementation of IPC measures has been essential to control the spread of infection in prisons and so minimise morbidity and mortality. However, for many (but not all) imprisoned people, these measures have resulted in isolation for much of the day with negative impacts on wellbeing. In future it will be important to ensure mental wellbeing is maintained and to involve the imprisoned people themselves in the development of effective interventions.